Alumina-supported sub-nanometer Pt10 clusters: amorphization and role of the support material in a highly active CO oxidation catalyst. Issue 10 (16th February 2017) - Yin, Chunrong; Negreiros, Fabio R.; Barcaro, Giovanni; Beniya, Atsushi; Sementa, Luca; Tyo, Eric C.; Bartling, Stephan; Meiwes-Broer, Karl-Heinz; Seifert, Sönke; Hirata, Hirohito; Isomura, Noritake; Nigam, Sandeep; et al.
Abstract : Bridging the support gap in heterogeneous ultrananocatalysis. Abstract : Catalytic CO oxidation is unveiled on size-selected Pt10 clusters deposited on two very different ultrathin (≈0.5–0.7 nm thick) alumina films: (i) a highly ordered alumina obtained under ultra-high vacuum (UHV) by oxidation of the NiAl(110) surface and (ii) amorphous alumina obtained by atomic layer deposition (ALD) on a silicon chip that is a close model of real-world supports. Notably, when exposed to realistic reaction conditions, the Pt10 /UHV-alumina system undergoes a morphological transition in both the clusters and the substrate, and becomes closely akin to Pt10 /ALD-alumina, thus reconciling UHV-type surface-science and real-world experiments. The Pt10 clusters, thoroughly characterized via combined experimental techniques and theoretical analysis, exhibit among the highest CO oxidation activity per Pt atom reported for CO oxidation catalysts, due to the interplay of ultra-small size and support effects. A coherent interdisciplinary picture then emerges for this catalytic system.